Summary Proof of Postponement of Debt Payment Obligations Through Act Number 37 of 2004 (Study of Decision Number 7/PDT.SUS-PKPU/2022/PN NIAGA MEDAN) - Simbolon, Alum; Chandra, Catherine Aureulli (Law Review, 2023)
Debt is a liability that arises through an agreement made between a debtor and a creditor. Debt is used as a basis for bankruptcy or for submitting a delay in payment of the debtor's debt. Summary Proof of Bankruptcy and Postponement of Debt Payment Obligations (PKPU) has actually been regulated in Article 8 paragraph (4) of Law Number 37 of 2004 and strengthened by Supreme Court Decision (MA) No.109/KMA/SK/IV/2020 concerning "Enforcement of the Handbook for Settlement of Bankruptcy Cases and PKPU". Summary Proof can be a reference for the Panel of Judges in granting PKPU applications by debtors or creditors to the Commercial Court. The PKPU application submitted through Decision Number 7/Pdt.Sus-PKPU/2022/PN Niaga was rejected by the Panel of Judges because the Panel of Judges considered that the non-fulfillment of the 'simple debt' requirement that had to be fulfilled was one of the burdens of proof in the application for PKPU.